Thinking philosophically with other thinkers - Valim, Ricardo (Sofia, 2026)
This research aims to investigate the extent to which the knowledge of indigenous peoples can contribute to the decolonization of thought. The methodology adopted is based on reading and analyzing the works of four authors whose contributions broaden conceptions of the world and question the hegemony of a single narrative. Of particular note is the writer Chimamanda Ngozi Adichie, whose critique of the “single narrative” denounces the risks of the homogenization of thought. In the Brazilian context, the voices of Ailton Krenak and Davi Kopenawa reaffirm the centrality of ancestry, spirituality and the relationship with nature as indispensable ontological foundations for understanding other forms of existence. Complementing these perspectives, Eduardo Viveiros de Castro's contribution, especially through the concept of Amerindian perspectivism, offers ways of accessing distinct forms of perception and knowledge. Friedrich Nietzsche's perspectivism will also be considered, due to its potential to broaden the critical vision and break with the closure in a single interpretative perspective. The conclusion is that the adoption of diverse epistemologies favors a more inclusive and plural philosophical dialogue, avoiding the confinement of reflection in a homogeneous vision. Recognizing multiple voices is essential for a richer and more complex understanding of reality, reaffirming the commitment to diversity and overcoming hegemonic views.
Keywords: decolonial; wisdom; indigenous; collective; contemporary